The Potential Development Analysis of Kampung City Toward Special Interest Tourism (Art, Culture, and Architcture) In The City Of Malang (Case Study: Heritage Village, Malang City) - Wiwik Dwi Susanti; Adibah Nurul Yunisya (Universitas Muhammadiyah Surakarta, 2022)
Special interest tourism is currently developing and becoming one of the favourite destinations for tourists. One of the conceptual developments of special interest tourism is by developing urban villages. The urban village is one of the miniatures of Indonesia which contains various kinds of cultural wealth, history, social values, etc. The Kayutangan heritage village is one of the urban villages developed by the Malang City Government as a special interest tourist destination in the middle of Malang City. The character of the urban village is enriched with historical, architectural, art and cultural values which have not been explored and optimized as a special interest tourist destination. The heritage village only emphasizes the colonization infrastructure legacy while other potentials have not been explored optimally. Through this qualitative research, the other four potentials (historical, architectural, art, and cultural values) will be explored in detail and provide educational values for the Kayutangan urban village tourism.